2020
DOI: 10.1177/2399808320956656
|View full text |Cite
|
Sign up to set email alerts
|

Are patterns of vacant lots random? Evidence from empirical spatiotemporal analysis in Chiba prefecture, east of Tokyo

Abstract: According to the Japanese government, vacant lots are randomly generated and accumulated (without being rebuilt after demolition) in the process of increasing vacant lots, a phenomenon called urban perforation. Urban perforation in urban areas may trigger a high degree of inefficiency in public infrastructure management. However, this observation lacks theoretical and empirical foundations, a lacuna to which this paper will focus on. Consequently, our research objectives are to confirm: (1) whether or not vaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In some extreme cases, like in Japan, we witness a gradual concentration within the urban areas of vacant plots, a phenomenon called urban perforation. Researchers are increasingly working on the spatial logics behind these perforations (Usui, 2019; Usui and Perez, 2020). From this perspective, our protocol shall also be able to provide insights regarding the spatial patterns related to the appearance of vacant plots and/or buildings.…”
Section: Discussion and Future Developmentsmentioning
confidence: 99%
“…In some extreme cases, like in Japan, we witness a gradual concentration within the urban areas of vacant plots, a phenomenon called urban perforation. Researchers are increasingly working on the spatial logics behind these perforations (Usui, 2019; Usui and Perez, 2020). From this perspective, our protocol shall also be able to provide insights regarding the spatial patterns related to the appearance of vacant plots and/or buildings.…”
Section: Discussion and Future Developmentsmentioning
confidence: 99%
“…In shrinking cities, 'dedensification' causes an oversupply of housing and infrastructure, which changes the shelter system of Vacant buildings that lack maintenance and repair over long periods are often demolished, giving rise to large amounts of vacant lots in shrinking cities, which resulted in fragmented urban landscapes and large amounts of marginal land (land that is difficult to cultivate using industrial agricultural techniques) (Schwarz et al 2016). Furthermore, Usui and Perez (2022) found that once vacant land accumulates randomly in urban areas, the process tends to continue, shifting urban vacant land from random to cluster generation, which can lead to severe urban perforation.…”
Section: Impacts On Urban Landscape and Structurementioning
confidence: 99%
“…Guo and Li 2019). With population loss as the most visible manifestation, urban shrinkage is accompanied by a reduction in urban economic activity and tax revenues (Slach et al 2019, Kocur-Bera andSzuniewicz 2021), resulting in increased vacant buildings and open space, oversupply of infrastructure, and inefficient public services (Schilling and Logan 2008, Wang and Immergluck 2019, Usui and Perez 2022, which significantly change the urban built environment. Changes in the built environment will raise ecological and sustainability concerns, but this process is often overlooked in shrinking cities.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of vacant and abandoned land is not always random but can have patterns (Usui and Perez, 2020). The geography of opportunity, a concept which presupposes that where individuals live affects their life outcomes and opportunities (Rosenbaum, 1995), it can be applied to the distribution of vacant and abandoned land across communities.…”
Section: Literature Reviewmentioning
confidence: 99%